2021
DOI: 10.3389/fspor.2021.608593
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Activity and Sport Participation Framework—A Policy Model Toward Being Physically Active Across the Lifespan

Abstract: The changing social and policy context in which sport is produced, delivered, and consumed is considered as a foundation for proposing a new integrated framework that incorporates participation in sport with participation in leisure-time physical activity (PA) more broadly. In order to position sport in the broader context of leisure-time PA, the concept of physical literacy is reviewed and integrated into the theoretical foundations of a new lifespan framework. It is argued that historically, sport policy lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 45 publications
1
25
0
1
Order By: Relevance
“…Whereas, the participation for boys decreased for those aged 5-9 years (decrease of 4%) and 10-14 years (decrease of 1%). It is promising that it is the early-sport adopters ages which have the opportunity to develop physical literacy for an active life (Westerbeek and Eime, 2021). Higher participation for children and young adolescents is consistent with other international studies (Woods et al, 2018;Kokko et al, 2019;Shull et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…Whereas, the participation for boys decreased for those aged 5-9 years (decrease of 4%) and 10-14 years (decrease of 1%). It is promising that it is the early-sport adopters ages which have the opportunity to develop physical literacy for an active life (Westerbeek and Eime, 2021). Higher participation for children and young adolescents is consistent with other international studies (Woods et al, 2018;Kokko et al, 2019;Shull et al, 2020).…”
Section: Discussionsupporting
confidence: 85%
“…As for the approach adopted to reduce physical inactivity, Westerbeek and Eime [ 21 ] suggest that a transition has been observed in the last few years regarding public policy models—from a sports-competition to a sports-recreation model that is fully integrated into individual’s daily lives. The sports-recreation model is known as a comprehensive sports ecosystem because, and similar to Muzenda et al’s [ 22 ] proposition, it considers trans-sectoral cooperation, and the incorporation of contributions from other sectors such as health, education, transportation, and urban planning to be essential.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, it was reported that 60% of 5- to 14-year-olds and 28% of 15-year-olds and older participated in at least one organised sport outside of school [ 22 ], whereas in American it was reported that approximately 50 to 56% of 6–12-year-olds and 54% of high school student participated in a sport at least once a year [ 23 ]. What is commonly seen, however, is that participation in sports and physical activity typically peaks between 10 and 14 years of age before declining between 15 and 19 years of age [ 24 , 25 ]. Youth athletes are characterised as either children or adolescents.…”
Section: Literature Reviewmentioning
confidence: 99%